Operational optimization of absorption column in capturing CO2 from flue gas in coal-fired power plant. Issue 9 (1st July 2021) - Panja, Palash; Pack, Tyrell Xavier; Deo, Milind
Abstract: The solvent scrubbing method is one of the promising technologies to capture CO2 from flue gas. In this technology, CO2 is absorbed from flue gas using a liquid solvent in an absorption column and subsequently, solvent and CO2 are separated in a stripper column. The recovered solvent from the stripper unit is recycled to an absorption unit along with the makeup of the fresh solvent. Aqueous monoethanolamine (MEA) is widely used as the solvent in this method. The cost of solvent for continuous makeup in the absorber is one of the major operating costs. The goal of this study is to minimize the flow rate of the MEA stream to capture the specified amount of CO2 from flue gas to reduce the operating cost. Various scenarios are simulated in commercial process plant simulator by varying the CO2 loading in lean MEA stream and absorber height. Flue gas compositions are obtained from the Rocky Mountain Hunter Power Plant (coal-fired), Utah, USA. We have shown that more than 80% CO2 is captured using absorber heights of 25–40 m and CO2 loading in MEA of 0.2 and less using the minimum flow rate of MEA. An insignificant amount of MEA (<0.2%) is lost from the absorption and stripper units. Other than the purchasing cost of the solvent, operating costs related to pumping, cooling, handling, etc. can be significantly reduced using the method developed in this study.